Contribution Cash Waqf Linked Sukuk in Community Welfare: Bibliometric Study and Perspective of Islamic Economics Academics - Nur Atiqah Maulad Murat; Nurul Jannah (Universitas Islam Negeri Sumatera Utara, 2025)
The purpose of this paper is to map the research theme that will answer how much the contribution of cash waqf linked sukuk is in the welfare of the community, besides that this paper also looks from an academic perspective. The method in this research is descriptive qualitative method with the type of literature study research, content analysis using FGD method as a complement to this research. So, the results of this paper show that based on the mapping of the literature paper above, it can be seen that this cash waqf linked sukuk has a major contribution to the welfare of the community, the returns from this CWLS fund can be used for educational scholarships, health service development, infrastructure development, and so on. In addition, academics also agree that waqf instruments have a major contribution to the country's economic development, so academics hope that this waqf instrument can be socialized and educated to the public in a massive way